Water Temperature Monitoring Device in Catfish Breeding Based on the Internet of Think - Alfarisi, Ahmat Sahman; Sujono, Sujono (SAINTEKBU, 2022)
The Internet of Things is a development of today's internet-based technology which has a concept to expand the benefits of objects connected to an internet connection continuously. For example, electronic objects, one of which is Arduino. This technology can provide information automatically and in real time. One use of this technological development in the fisheries sector is a pond water monitoring system. In practice, catfish farmers still monitor conventionally, namely by visiting fish ponds. This affects the time efficiency and effectiveness of fish cultivation work. In this research, a tool was developed to help monitor and control the water quality of catfish ponds based on the Internet of Things. The device needed is a temperature sensor. Data from these sensors is recorded by Arduino and then processed into information according to user needs via the internet automatically. Furthermore, this data can be displayed on various platforms, including the mobile web model. The test results show that the development of Internet of Things technology in this system can help farmers monitor water quality automatically. The developed automation system promises to increase success in catfish cultivation.